The unfolded protein response-glutathione metabolism axis: a novel target of a cycloruthenated complexes bypassing tumor resistance mechanisms - Riegel, Gilles; Orvain, Christophe; Recberlik, Sevda; Spaety, Marie-Elodie; Poschet, Gernot; Venkatasamy, Aina; Yamamoto, Masami; Nomura, Sachiyo; Tsukamoto, Tetsyua; Masson, Murielle; Gross, Isabelle; Le Lagadec, Ronan; et al. (Cancer letters, 2024)
Platinum-based drugs remain the reference treatment for gastric cancer (GC). However, the frequency of resistance, due to mutations in TP53 or alterations in the energy and redox metabolisms, impairs the efficacy of current treatments, highlighting the need for alternative therapeutic options. Here, we show that a cycloruthenated compound targeting the redox metabolism, RDC11, induces higher cytotoxicity than oxaliplatin in GC cells and is more potent in reducing tumor growth in vivo. Detailed investigations into the mode of action of RDC11 indicated that it targets the glutathione (GSH) metabolism, which is an important drug resistance mechanism. We demonstrate that cycloruthenated complexes regulate the expression of enzymes of the transsulfuration pathway via the Unfolded Protein Response (UPR) and its effector ATF4. Furthermore, RDC11 induces the expression of SLC7A11 encoding for the cystine/glutamate antiporter xCT. These effects lead to a lower cellular GSH content and elevated oxygen reactive species production, causing the activation of a caspase-independent apoptosis. Altogether, this study provides the first evidence that cycloruthenated complexes target the GSH metabolism, neutralizing thereby a major resistance mechanism towards platinum-based chemotherapies and anticancer immune response.
Online verfügbar: 28. Januar 2024, Artikelversion: 15. Februar 2024
Gesehen am 01.08.2024